Digital Storytelling in Cultural and Heritage Tourism: A Review of Social Media Integration and Youth Engagement Frameworks - Kittichai Kasemsarn; Farnaz Nickpour (Heritage, 2025)
Digital storytelling in cultural and heritage tourism offers significant potential for youth engagement through social media platforms. However, current digital storytelling frameworks illustrate research gaps in integrating digital storytelling guidelines with social-media-specific requirements. Therefore, this review aims to develop an integrated digital storytelling for social media framework that extends traditional digital storytelling guidelines with four additional elements of contemporary digital engagement. The investigation employs bibliometric analysis through VOSviewer software version 1.6.20 to examine four paired domains: digital storytelling and cultural tourism, digital storytelling and social media, youth and cultural tourism, and youth interaction with digital storytelling through social media. Results revealed thematic clusters informing the development of four new framework elements: (1) social media platform integration, (2) multimedia engagement, (3) community participation, and (4) cultural authenticity. This review contributes to the knowledge by advancing digital storytelling theory through social-media-specific elements, providing methodological innovation through comprehensive domain analysis, and offering practical implementation strategies for cultural tourism practitioners.
Keywords: Digital Storytelling and Education; Literacy, Media, and Education